Desenvolvimento de um novo aplicativo mobile para realização de exames em fisioterapia - Schneider, Stefan Guilherme (2024)
The present work aimed to develop a mobile application with theoretical and practical support to be used by undergraduate Physiotherapy students and professionals in the field during clinical examinations. The proposal came from an empirical problem presented by the project collaborator and professor at the Federal University of Pampa (UNIPAMPA) who, while supervising the students during the internship period, realized that most of them did not remember the procedures for carrying out the physiotherapeutic exams that learned during the course. As mobile devices are currently the main means by which people access the internet and due to the great advances made in the hardware of these devices, applications have become quick and efficient solutions to overcome everyday situations. The App had a theoretical basis to assist in carrying out exams and spreadsheets with voice filling to speed up data collection from medical records. In addition to providing a teaching and learning tool, the application aimed to make the service process more practical and efficient. The application was developed using the IDE Android Studio, a Google tool for Android development, and validation was carried out through a Likert-type SUS questionnaire with 21 physiotherapy students from UNIPAMPA who used the App. The results demonstrated that the application aroused confidence in users who, for the most part, considered the system to be not very complex, not very complicated, easy to use and quick to learn. Although the application has not been finalized, users found few inconsistencies in the system and stated that they would like to use it frequently in their educational and professional practices. Finally, after analyzing the results, it was found that, according to the SUS questionnaire score corresponding to the methodology used, the App has the possibility of usability classification between Excellent and Best Imaginable.